Magical Realism and Its Influence on the Main Characters’ Environmental Awareness in Helen Dunmore’s Ingo - Prasetyo, Norma Indah Dwi (Universitas Negeri Surabaya, 2025)
Helen Dunmore’s Ingo is a novel that employs the elements of magical realism to explore environmental issues. This study focuses on Ingo because its fantastical aspects reflect characteristics of magical realism and appear to impact the environmental awareness of its main characters. This study has two main aims: to examine how magical realism is depicted in the novel and to investigate its influence on the main characters’ awareness of the environment. To accomplish this, the study applies Wendy B. Faris’s five key features of magical realism: the presence of irreducible magic, the extraordinary world, unsettling doubts, the fusion of two different worlds, and the disruption of time, identity, and space. The primary source is the 2009 e-book edition of Ingo published by HarperCollins, with collected data drawn from narrative passages and dialogues involving the three main characters, namely Sapphire, Conor, and Faro. The analysis follows the TEEL (Topic, Evidence, Explanation, Link) structure and is supported by relevant previous studies. The findings reveal that Ingo exhibits all five of Wendy B. Faris’s magical realism elements, and its extraordinary elements effectively highlight environmental concerns, ultimately shaping the main characters’ environmental awareness.